MORPHOLOGICAL ANALYSIS OF COMPOUNDING IN THE NOVEL THE BURNING MAZE: THE TRIALS OF APOLLO BY RICK RIORDAN - Mulyaningtyas, Lintang Ayu; Khoirunnisa, Avicenia Nasywa; Kusuma, Novelia Salsa Dara; Jumanto, Jumanto (BASIS (Bahasa dan Sastra Inggris), 2024)
This research concerned a morphological analysis of compounding within The Burning Maze: The Trials of Apollo by Rick Riordan. This study morphologically described the importance of language in conveying deep emotion and thematic richness. This descriptive qualitative linguistic research employed the observation and auto-expert judgment methods for the data collection and morphological note-taking techniques for the data analysis. The results revealed patterns of word combinations that contributed to the linguistic richness and depth of the themes. The discussion interpreted these findings in the context of the novel’s storytelling, providing further understanding of the role of morphology in character development and plot complexity. The results showed that compounding in The Burning Maze: The Trials of Apollo by Rick Riordan had a combination of elements with the form of the Noun (N) + Verb (V); Noun (N) + Noun (N); Verb (V) + Verb (V); Adjective (Adj) + Noun (N); Verb (V) + Noun (N); Adverb (Adv) + Noun (N); Noun (N) + Adverb (Adv); Adjective (Adj) + Verb (V); Adjective (Adj) + Adjective (Adj); Adverb (Adv) + Adjective (Adj); Verb (V) + Adverb (Adv); Noun (N) + Adjective(Adj); Verb (V) + Adjective (Adj). Besides revealing linguistic nuances in literary works, this research has strived to deepen our understanding of the intricate layers within literature, showcasing how the careful selection of words enhanced the reader’s immersive journey into the literary landscape.